The Hennepin Ketamine Study Investigators' Reply. Issue 2 (3rd May 2019) - Ho, Jeffrey D.; Cole, Jon B.; Klein, Lauren R.; Olives, Travis D.; Driver, Brian E.; Moore, Johanna C.; Nystrom, Paul C.; Arens, Annie M.; Simpson, Nicholas S.; Hick, John L.; Chavez, Ross A.; Lynch, Wendy L.; et al.
Abstract : We read with interest the recent editorial, "The Hennepin Ketamine Study, " by Dr. Samuel Stratton commenting on the research ethics, methodology, and the current public controversy surrounding this study. 1 As researchers and investigators of this study, we strongly agree that prospective clinical research in the prehospital environment is necessary to advance the science of Emergency Medical Services (EMS) and emergency medicine. We also agree that accomplishing this is challenging as the prehospital environment often encounters patient populations who cannot provide meaningful informed consent due to their emergent conditions. To ensure that fellow emergency medicine researchers understand the facts of our work so they may plan future studies, and to address some of the questions and concerns in Dr. Stratton's editorial, the lay press, and in social media, 2 we would like to call attention to some inaccuracies in Dr. Stratton's editorial, and to the lay media stories on which it appears to be based. Ho JD, Cole JB, Klein LR, Olives TD, Driver BE, Moore JC, Nystrom PC, Arens AM, Simpson NS, Hick JL, Chavez RA, Lynch WL, Miner JR. The Hennepin Ketamine Study investigators' reply. Prehosp Disaster Med . 2019;34(2):111–113